The Problem of Man and His Perfection Abdurahman Jamiy in their Views - Mirzoyeva Nigora Shavkatjonovna (Research Parks Publishing LLC, 2021)
This article describes the philosophical interpretation of the humanist views on the culture, way of life and social life of the 15th century by the famous scientist Mavlono Abdurahmon Jami. The main part of his creative activity is dominated by the spirit of teaching, and most of his works reveal the inner and outer world of man philosophically, mystically and scientifically.